(untitled) (Tigbauan, Iloilo, Philippines, 2015)
In order to promote and augment regional initiatives on resource enhancement and sustainable aquaculture practices, and to contribute to poverty alleviation, livelihood and food security, the SEAFDEC Aquaculture Department held the International Workshop on Resource Enhancement and Sustainable Aquaculture Practices in Southeast Asia in 2014. Papers from two plenary speakers, reports from SEAFDEC member countries’ representatives as well as contributed papers on sustainable aquaculture and resource enhancement in the region were presented and are now compiled in this conference proceedings. Finally, SEAFDEC/AQD acknowledges the Government of Japan for fully supporting the workshop and this publication.
Keywords: Nuôi trồng thủy sản bền vững,Sustainable aquaculture; Đông Nam Á,Southeast Asia